"Sick-but-not-dead": multiple paths to catecholamine deficiency in Lewy body diseases. (1st November 2020) - Goldstein, David S.
Abstract: Profound depletion of the catecholamines dopamine (DA) and norepinephrine in the brain, heart, or both characterizes Lewy body diseases such as Parkinson disease, dementia with Lewy bodies, and pure autonomic failure. Although one might presume that catecholamine deficiency in these disorders results directly and solely from loss of catecholaminergic neurons, there is increasing evidence that functional abnormalities in extant residual neurons contribute to the neurotransmitter deficiencies—the "sick-but-not-dead" phenomenon. This brief review highlights two such functional abnormalities—decreased vesicular sequestration of cytoplasmic catecholamines and decreased catecholamine biosynthesis. Another abnormality, decreased activity of aldehyde dehydrogenase, may have pathogenetic significance and contribute indirectly to the loss of catecholamine stores via interactions between the autotoxic catecholaldehyde 3, 4-dihydroxyphenylacetaldehyde and the protein alpha-synuclein, which is a major component of Lewy bodies. Theoretically, chronically repeated stress responses could accelerate these abnormalities, via increased exocytosis and neuronal reuptake, which indirectly shifts tissue catecholamines from vesicular stores into the cytoplasm, and via increased tyrosine hydroxylation, which augments intra-cytoplasmic DA production. The discovery of specific paths mediating the sick-but-not-dead phenomenon offers novel targets for multi-pronged therapeutic approaches.